At give stemme til det usynlige - Welz, Claudia (Dansk Teologisk Tidsskrift, 2012)
The present article discusses theological questions arising through the phenomenon and praxis of prayer: What are the features of different genres of prayer such as praise and lament, confession and intercession, and how can the relation between semantics and pragmatics within the performance of prayer be characterized if the language of prayer does not only embrace self-involving speech acts in an agonic process leading to the supplicant’s self-transformation, but also silent gestures, deeds and attitudes? What is the relation between speech and silence in prayer? To what extent is it legitimate to determine prayer as a ‘dialogue’ with God? Given that God does not speak with a ‘voice’ that can be heard acoustically, the question is also how one can know whether it is God or someone else ‘speaking’ to a person. Texts by Luther, Kierkegaard, Levinas, Derrida, Chrétien, Wittgenstein, Phillips, Casper and Brümmer provide the basis for this discussion.